Implementation of Revolution in Military Affairs in the Russian and Ukrainian Wars - Nazirah, Nazirah; Zaini, Ansori; Suseto, Buddy (Formosa Journal of Applied Sciences, 2024)
This research examines the implementation of the Revolution in Military Affairs (RMA) concept in the Russian-Ukrainian War, focusing on its impact on military strategies and operational tactics. RMA involves transformative changes in military technology, doctrine, and organization, reshaping modern warfare. In this conflict, elements such as drone technology, cyber warfare, and network-based weapon systems have been pivotal. Using a descriptive analysis method, the study collected data from military reports, journal articles, and news sources to identify how RMA was applied by both sides and evaluate the influence of modern technology on the conflict's outcomes. The analysis focused on Unmanned Aerial Vehicles (UAVs), electronic warfare systems, and network-based defenses, which intensified the complexity and pace of operations. The findings reveal that both Russia and Ukraine adopted RMA elements, albeit with varying capabilities and effectiveness.